2022
DOI: 10.1021/acs.est.2c01639
|View full text |Cite
|
Sign up to set email alerts
|

Amine-Enhanced Methanesulfonic Acid-Driven Nucleation: Predictive Model and Cluster Formation Mechanism

Abstract: Atmospheric amines are considered to be an effective enhancer for methanesulfonic acid (MSA)-driven nucleation. However, out of the 195 detected atmospheric amines, the enhancing potential (EP) has so far only been studied for five amines. This severely hinders the understanding of the contribution of amines to MSA-driven nucleation. Herein, a two-step procedure was employed to probe the EP of various amines on MSA-driven nucleation. Initially, the formation free energies (ΔG) of 50 MSA-amine dimer clusters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…3,4 The precise way that gaseous vapor comes together to form prenucleation complexes, which eventually build to aerosols, and thus form CCN, is a very active area of research. 3,5–74 Much of this activity is driven by the uncertainty in how much aerosols and clouds will impact global warming. 75,76 While it is thought that in general more aerosols will lead to a cooling effect, the uncertainty in our knowledge exceeds the actual size of the predicted cooling.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The precise way that gaseous vapor comes together to form prenucleation complexes, which eventually build to aerosols, and thus form CCN, is a very active area of research. 3,5–74 Much of this activity is driven by the uncertainty in how much aerosols and clouds will impact global warming. 75,76 While it is thought that in general more aerosols will lead to a cooling effect, the uncertainty in our knowledge exceeds the actual size of the predicted cooling.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the only MSA− base system that has definitively been proven to lead to strong NPF is the MSA−guanidine system. 30 We recently showed that (MSA) 1−2 (base) 1−2 clusters have an extremely low cluster formation potential; 31 however, this deficiency could be alleviated by just having a single SA molecule present in the cluster. 32 A similar conclusion was realized by Bork et al 33 in the quantum chemical and cluster dynamics study of (SA) n (MSA) m (DMA) l clusters, with n + m ≤ 3 and l ≤ 2.…”
Section: Introductionmentioning
confidence: 99%
“…This is further corroborated by quantum chemical studies of MSA–ammonia, MSA–methylamine, and MSA–dimethylamine systems, which all showed relatively low particle formation rates. To the best of our knowledge, the only MSA–base system that has definitively been proven to lead to strong NPF is the MSA–guanidine system . We recently showed that (MSA) 1–2 (base) 1–2 clusters have an extremely low cluster formation potential; however, this deficiency could be alleviated by just having a single SA molecule present in the cluster .…”
Section: Introductionmentioning
confidence: 99%
“…Recently Liu et al built a quantitative structure–activity relationship model and predicted GUA to form very strong interactions with MSA, and thus be possibly the strongest enhancer in the MSA-driven NPF under atmospheric conditions. 19 Clusters where the number of MSA is greater than GUA molecules are stable, which might be due to the lower vapor pressure of MSA (5.6 × 10 −7 atm in 298 K) than that of GUA, and perhaps the volatility of participating monomers could be used as a predictor for non-neutral acid-to-base ratio in salt particles. Thus, under acid-rich conditions, MSA–GUA particles are likely to be acidic.…”
Section: Resultsmentioning
confidence: 99%
“…Here our model system contains three different acids: sulfuric acid (SA), methanesulfonic acid (MSA), and nitric acid (NA) and one base: guanidine (GUA). Recently SA-GUA and MSA-GUA systems have been shown to lead to efficient particle formation, [17][18][19] and here NA-GUA clusters are also found to be relatively stable. While the role of hydration in the cases of acids with ammonia or amines has been previously investigated, [20][21][22] it has not been studied in the case of guanidine.…”
Section: Introductionmentioning
confidence: 92%